Does increasing physician volume in primary healthcare facilities under the hierarchical medical system help reduce hospital service utilisation in China? A fixed-effects analysis using province-level panel data - Bin Zhu; Xiaotong Li; Pei Xie; Huiwen Xu; Fang Du; Hankun Wang; Xinxin Han (BMJ Open)
Objective To examine whether increases in physician volume in primary healthcare facilities are associated with reduced utilisation of hospital outpatient and inpatient services after China facilitated the establishment of the hierarchical medical system.Design We used a two-way fixed-effects regression to examine the association between the annual number of physicians in primary healthcare facilities and that of patient visits per physician, inpatient admissions and total expenses per outpatient visit in public hospitals during 2010–2014 and 2015–2019. Variables were log transformed to ensure the normal distribution of the data.Setting Province-level data of all 31 provinces in mainland China from 2010 to 2019 were collected from the China Health Statistics Yearbook published by the China Health Commission.Participants All 31 provinces in mainland China.Primary and secondary outcome measures The annual number of outpatient visits per physician, hospital admission and total expenses per outpatient visit in public hospitals.Results During 2015–2019, we found that, on average, a 1% increase in the number of primary healthcare physicians was accompanied by a 0.19% (95% CI −0.33% to −0.05%) reduction in the annual number of visits per physician in public hospitals, and a 0.31% (95% CI −0.52% to −0.10%) reduction in patient visits in city-administered hospitals. No significant associations were found between 2010 and 2014. We also did not observe any significant associations between primary healthcare physician volume and hospital admissions or outpatient expenses during neither 2010–2014 and 2015–2019.Conclusions In the context of the hierarchical medical system, enhancing physician volume in primary healthcare facilities helps reduce outpatient visits in public hospitals, especially city-administered hospitals. However, more efforts are required to be continuously made to improve primary healthcare capacity to avoid preventable hospital admissions and outpatient expenses.